You are on page 1of 10

PHYS 221A Assignment 1 Solutions

Jake Bian
September 30, 2015

Contents
1 Lorentz Group Orbits

2 Lorentz Map on the Minkovski Metric

3 Lorentz Algebra I: Skew-Symmetry


3.1 Skew-Symmetry . . . . . . . . . . . . . . . . . . . . . . . . . . . .
3.2 Geometric Intuition for Basis of Generators . . . . . . . . . . . .

3
3
5

4 Lorentz Algebra II: Generators and Structure Constants


4.1 a. Vector fields from Lie algebra . . . . . . . . . . . . . . . . . .
4.2 b. The Lorentz Algebra . . . . . . . . . . . . . . . . . . . . . . .

5
5
6

5 Lorentz Algebra III. Boost-Rotation Decomposition

6 Hamiltonian and Number Operator

Lorentz Group Orbits

Consider vector space V ' R4 , let V denote its dual vector space. Let ( )
denote a basis for V , and (dx ) the dual basis in V . Define a symmetric
2-tensor V V as
= dt dt +

3
X

dxi dxi

(1.1)

i=1

Let G the Lorentz group. G has a well-defined action on V as a linear map


G V V, (, v) 7 v

(1.2)

where in the last arrow is to be read as a linear map V V . The full


Lorentz Group is the set of all linear maps : V V with the property

(v, v) = (v, v)

(1.3)

We consider the orbit Bv of G at v V , explicitly


Bv {v | G}

(1.4)

By 1.3, Bv is also given by


Bv = {w V | (w, w) = (v, v)}

(1.5)

Rewriting this in components we find


Bv = {w V | (w0 )2 +

3
X

(wi )2 = (v, v)}

(1.6)

i=1

Hence Bv V is a 3-hyperboloid embedded in R4 . Observe that the topology


of the Bv is sensitive to (v, v), namely
For (v, v) > 0 Bv is a one-sheeted hyperboloid

(1.7)

For (v, v) < 0 Bv is a 2-sheeted hyperboloid

(1.8)
Now assume v 0 > 0 - that is, v is some point on Bv above the t = 0 plane.
We also restrict ourselves to the component of G connected to the identity. The
following observations follow from the pictures above
When (v, v) > 0, there exist smooth 1-dimensional curves on Bv which
connect v, a point above the t = 0 plane, to a point v 0 , below the t = 0
plane. Since Bv is the orbit of the Lorentz group, these 1-dimensional
curves are the orbits of smooth 1-parameter groups of Lorentz transformations starting from the identity taking v 7 v 0 with v 00 < 0.
1 These

are public-domain pictures from Wikipedia

When (v, v) < 0, there are no curves connecting the upper half of the
hyperbloid to the bottom half. Therefore there cannot be smooth 1parameter families of Lorentz transformation which takes v below the
t = 0 plane. There are no other transformations that can take v below
the plane because were restricted to the component of the Lorentz group
connected to the identity, in particular reflection across a plane is not a
smooth transformation, hence lies on another component of the Lie group
G.
This is the desired result.

Lorentz Map on the Minkovski Metric

In the same nomenclature as above, observe


(v, v) = [v v]

(2.1)

= [ (v v)] = ( )[v v]

(2.2)

= ( )(v, v)

(2.3)

Comparing this with (v, v) = (v, v), we get


=

(2.4)

In components, this is exactly


=

(2.5)

as desired.

Lorentz Algebra I: Skew-Symmetry

3.1

Skew-Symmetry

Consider now a Lorentz transformation of the form


= 1 +

(3.1)

= 1 + (1 + 1) + O(2 )

(3.2)

compute

Plug this into result of the last problem 2.5, dropping the O(2 ) term we
find
(1 + (1 + 1)) =

(3.3)

Therefore
(1 + 1) = 0

(3.4)

Acting this (0, 2) tensor on 2 vectors u, v V yields


0 = (1 + 1)[u v] =

(3.5)

= (1 )[u v] + (1 )[u v]

(3.6)

= (u, v) + (u, v)

(3.7)

Let denote the metric transpose (or metric pullback) of . That is, is
a linear operator on V such that
( u, v) = (u, v)

(3.8)

Using the metric pullback in our previous equation, we get


0 = ( u, v) + (u, v) = ( u, v) = (u, v)

(3.9)

This holds for arbitrary u, v, V , degeneracy of the metric implies


=

(3.10)

This is the coordinate-independent version of the desired result. To reconcile


this with the components version suggested in the problem, consider simply the
component form of the metric pullback. Observe first
(u, v) = ab b ua v , ( u, v) = b ba ua v

(3.11)

where weve labelled the dummy indices so that we can factor out the vector components easily. The definition of the metric pullback 3.8 says the two
quantities above are equal, hence
b ba = ab b

(3.12)

In the usual physicists notation the metric lowers an index, the equation
becomes
a = a

(3.13)

Using our coordinate-independent result = , we finally obtain


a = a

(3.14)

This is the desired result in component form. One can apply the metric
inverse twice to convert this last equation into an identical result about tensors
with pure-vector (upper) indices.

3.2

Geometric Intuition for Basis of Generators

By freshman linear algbera, the set of skew-symmetric linear maps on V Rd


forms a vector space Sd of dimension d(d 1)/2.
Observe d(d 1)/2 = d choose 2. There is an intuitive explanation for this:
an arbitrary (Lorentzian) rotation is a composition of (Lorentzian) rotations
which leave a particular dimension 2 plane fixed. This picture can also be seen
very easily from the explicit formula for the vector field generated by Lorentz
group in the next section.
In particular in d = 3 + 1, there are 3 independent rotations and 3 independent boosts.

Lorentz Algebra II: Generators and Structure


Constants

4.1

a. Vector fields from Lie algebra

In the previous section we showed that the (0, 2) tensor


ab dxa dxb

V V is skew symmetric. This means


in fact lives in the subspace V V

a
b
V V , for wich a basis is {dx dx }, and in these coordinates we label the
components of the tensor as

= ab dxa dxb

(4.1)

We ultimately want to act this on a vector to obtain a vector field. Hence we


want construct a linear operator - or a rank (1, 1) tensor in V V . Colloquially
we want to raise a index. We do this with the isomorphism given by the inverse
metric V V
: V V

1 : V V V V

(4.2)
(4.3)

We define the tensor as


under the above map

1 [
] = ab dxa [dxb ] = ab b dxa = a dxa (4.4)
where we took the usual definition of the wedge product between a V and
b V as
a b a b b a

(4.5)

where again denotes vector space dual. We compute the contraction of


with a vector x x V yields
kx [x 1] = ab dxa b [x 1]
5

(4.6)

For the sake of clarity Ill go painfully slow here


dxa b [x 1] = (dxa b dxb a )[x 1]
a

= dx [x ] b dx [x ] a
a

= x b x a

(4.7)
(4.8)
(4.9)

Using this in the expression above


kx = [x 1] = ab (xa b xb a )

(4.10)

Observe the metric inner product in the first component is invariant under
the following shifting of indices
ab (xa b xb a ) 7 ab (xa b xb a )

(4.11)

This is desired result. To get the exact form of the result as suggested in
the problem statement, recall is related to an element of G by Lie algbera
exponentiation, infinitesmally we can consider a Lorentz group element infinitesmally close to the identity
= 1 +

(4.12)

And define the infinitesmall change on some vector v V as


v v v = v

(4.13)

In components, this last expression is then


v = ab (xa b xb a )v

(4.14)

This is the desired result (up to a redefinition of tensors by constant scalings).

4.2

b. The Lorentz Algebra

We compute [Luv , Lab ] by brute force.


Luv Lab = Luv (xa b xb a ) = Luv (xa )b Luv (xb )a

(4.15)

= (x (xa ) x (xa ))b + (x (xb ) x (xa ))a

(4.16)

= (x a x a )b + (x b x b )a

(4.17)

Under a, b, the above equation reads


Lab Luv = (xa b xb a ) + (xa b xb a )b
Hence

(4.18)

[Luv , Lab ] = [(x a x a )b + (x b x b )a ] [(xa b xb a ) + (xa b xb a )b ]


(4.19)
= a (x b xb m u) + a (xb x b ) + b (x a xa ) + b (x a xa )
(4.20)
= a Lb + a Lb + b La + b La

(4.21)

Lorentz Algebra III. Boost-Rotation Decomposition

We proceed directly to the tedious and uninspiring brute force computation.


1
iab jcd [M ab , M cd ]
4
1
= iab jcd (( ac M bd a b) c d)
4

[Ji , Jj ] =

(5.1)
(5.2)

Rewrite the first term using an identity for the levi-civita symbol
1
1
iab jcd ac M bd = icb jcd M bd = (cbi cdj )M bd
4
4
1
1
1
= (bd ij bj id )M bd = Mbb ij M ji = M ij
4
4
4

(5.3)
(5.4)

where in the last equality we used the fact that M ab is skew symmetric, and
therefore has vanishing diagonals. Repeating this for each term in the original
expression and taking the sum, we find
[Ji , Jj ] = M ij

(5.5)

Now observe
1
kab kcd M cd
2
1
= (ac bd ad bc )M cd
2
1
= (M ab M ba ) = M ab
2

abk Jk =

(5.6)
(5.7)
(5.8)

This is exactly what the commutator above evaluated to, hence


[Ji , Jj ] = M ij = ijk Jk

(5.9)

The remaining commutators can be verified in an exactly analogous and


equally tedious manner. For completeness we type it below.
7

Consider commutator
1
1
iab [M ab , M j0 ] = iab (( aj M b0 a b) j 0)
2
2
the first term looks like
[Ji , Kj ] =

(5.10)

1
1
1
iab ( aj M b0 ) = ijb M b0 = ijb Kb
(5.11)
2
2
2
the j i part vanishes because each term is multiplied by a factor like a0 ,
which vanishes because a > 0. The b a part yields an identical term. Hence
[Ji , Kj ] = ijb Kk

(5.12)

as desired. Finally, consider


[Ki , Kj ] = [M i0 , M j0 ] = (g ij M 00 g 0j M i0 ) (g i0 M 0j g 00 M ij )
0j

0i

0i

= (g M ) (g M
00

=g M

ij

= M

ij

0j

00

ij

+g M )

= ijk Jk

(5.13)
(5.14)
(5.15)

where terms like gi0 vanish because i, j > 0 and gab is diagonal. We also
used the fact g 00 = 1 for flat Minkovski metric.

Hamiltonian and Number Operator

This is yet another tedious computation. We simplify our notation by writing


H = H0 + H1

(6.1)

where
Z
H0

d3 x a Aa|x

(6.2)

h
2 + U (x) and the interaction part is
where A(x) 2m
Z
H1 d3 xd3 y V (x y)a (x)a (y)a(y)a(x)

(6.3)

We first verify the usual commutators of the number operator with the ladder
operators
Z
[N, a(x)] =
Z
=
Z
=

d3 y[a a|y , a(x)]

(6.4)

d3 y a (y)[a(y), a(x)] + [a (y), a(x)]a(y)

(6.5)

d3 y (x y)a(y) = a(x)

(6.6)

identically

[N, a (x)] =

Z
Z

=
Z
=

d3 y[a a|y , a (x)]

(6.7)

d3 ya (y)[a(y), a (x)] + 0

(6.8)

a (y)(y x) = a (x)

(6.9)

where we used the known commutation relations between the ladder operators. Also observe
[N, A] = 0

(6.10)

where A was defined as above, where the term involving the derivative vanishes because N has no x dependence. Now compute
Z
[N, H0 ] =

d3 x a [N, Aa] + [N, a ]Aa

d x [N, a Aa] =

(6.11)

d3 x a (A[N, a] + [N, A]a) + [N, a ]Aa (6.12)

d3 x a A(a) + a Aa = 0

=
=

(6.13)

To compute the remaining term, we use a trick. Make the following rearrangement using commutation relations
a (x)a (y)a(y)a(x) = a (x)a (y)a(x)a(y)

(6.14)

= a (x)([a (y), a(x)] + a(x)a (y))a(y)

(6.15)

= a (x)((y x))a(y) + a (x)(a(x)a (y))a(y)

= (y x)a (x)a(y) + a (x)a(x)a (y)a(y)

(6.16)
(6.17)

Lets call the integrand of the number operator n(x), that is


n(x) a (x)a(x)
observe N =

(6.18)

d x n(x) and
Z
[N, n(x)] =

d3 y [n(y), n(x)] = 0

(6.19)

which can be verified as above with the commutation relations. Putting


together with equations above yields

Z
H1 =

d3 xd3 y V (x y)a (x)a (y)a(y)a(x)

(6.20)

d3 xd3 y V (x y)((y x)a (x)a(y) + a (x)a(x)a (y)a(y))


Z
Z
= d3 x V (0)a (x)a(x) + d3 xd3 ya (x)a(x)a (y)a(y))
Z
Z
= d3 xV (0)n(x) + d3 xd3 y n(x)n(y)
Z
= V (0)N + d3 xd3 y n(x)n(y)

(6.21)
(6.22)
(6.23)
(6.24)

Finally
Z
[N, H1 ] = V (0)[N, N ] +

d3 xd3 y [N, n(x)n(y)] =

d3 xd3 y n(x)[N, n(y)] + [N, n(x)]n(y) = 0


(6.25)

Hence
[N, H] = [N, H0 + H1 ] = [N, H0 ] + [N, H1 ] = 0

10

(6.26)